2016
DOI: 10.1101/070375
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reward-based training of recurrent neural networks for cognitive and value-based tasks

Abstract: Trained neural network models, which exhibit many features observed in neural recordings from behaving animals and whose activity and connectivity can be fully analyzed, may provide insights into neural mechanisms. In contrast to commonly used methods for supervised learning from graded error signals, however, animals learn from reward feedback on definite actions through reinforcement learning. Reward maximization is particularly relevant when the optimal behavior depends on an animal's internal judgment of c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 81 publications
2
43
0
Order By: Relevance
“…Moreover, trial-by-trial variability in the activity of each group of neurons correlates with variability in choices (Padoa-Schioppa, 2013;Conen and Padoa-Schioppa, 2015). Computational models show that the cell groups identified in OFC are sufficient to generate binary choices (Rustichini and Padoa-Schioppa, 2015;Friedrich and Lengyel, 2016;Song et al, 2017;Zhang et al, 2018), and the population dynamics is consistent with decision making (Rich and Wallis, 2016). These results suggest that economic decisions might be formed within the OFC (Padoa-Schioppa and , but causality has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, trial-by-trial variability in the activity of each group of neurons correlates with variability in choices (Padoa-Schioppa, 2013;Conen and Padoa-Schioppa, 2015). Computational models show that the cell groups identified in OFC are sufficient to generate binary choices (Rustichini and Padoa-Schioppa, 2015;Friedrich and Lengyel, 2016;Song et al, 2017;Zhang et al, 2018), and the population dynamics is consistent with decision making (Rich and Wallis, 2016). These results suggest that economic decisions might be formed within the OFC (Padoa-Schioppa and , but causality has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, neuronal dynamics in OFC during economic decisions reflect an internal deliberation 16 . Complementing these experimental findings, theoretical work showed that neural networks whose units match the cell groups identified in OFC can generate binary decisions ( Fig.1ab) [17][18][19][20][21] . Collectively, these results appear to lay the foundations for a satisfactory understanding of the mechanisms underlying economic decisions.…”
Section: Introductionmentioning
confidence: 69%
“…September 18, 2019 26/35 Clopath, 2017]. Another approach may be to use a reinforcement learning paradigm, rather than the gradient of an error signal, to train the network system [Song et al, 2017]. However, the latent dynamics underlying task learning uncovered here evolve over a longer timescale than the learning dynamics underlying network training, so findings are likely not impacted by different training protocols.…”
Section: Discussionmentioning
confidence: 99%